Factors Predicting Stroke Preventive Behaviors in Diabetes Mellitus Patients with Hypertension - Aumaor, Thamakorn; Khungtumneam, Kamontip; Dejkun, Adchara; Soynahk, Chutima; Bhuchaeng, Direk (Journal of Phrapokklao Nursing College, Chanthaburi, 2024)
This predictive correlational research aimed to explore the factors predicting stroke preventive behaviors in diabetes mellitus patients with hypertension. The samples were 100 diabetes mellitus patients with hypertension who received medical services at Nongprue Sub-district Health Promoting Hospital, Bang Phli District, Samut Prakan Province. The research instruments included a general and health status information questionnaire, a factor influencing stroke preventive behavior questionnaire with the reliabilities in the range of .79–.89, and a stroke preventive behavior questionnaire with a reliability of .71. Data were collected from September to November 2023. Statistics used for data analysis included frequency, percentage, mean, standard deviation, and stepwise multiple regression analysis. The research results revealed that the diabetes mellitus patients with hypertension demonstrated overall mean score of stroke preventive behaviors at a good level (M = 3.14, SD = .25). Perceived severity, perceived benefits, and cues to action could statistically significantly explain stroke preventive behaviors in diabetes mellitus patients with hypertension about 45.60% of the variance (R2 = .456, p < .001). The most predicting factor was perceived benefits (Beta = .341, p < .01). This research suggests that nurses and healthcare workers should provide activities to promote stroke preventive behaviors in diabetes mellitus patients with hypertension, focusing on the enhancement of perceived severity and perceived benefits among the patients and their relatives.